1996
DOI: 10.1002/art.1780390616
|View full text |Cite
|
Sign up to set email alerts
|

Risk of osteoarthritis associated with long‐term weight‐bearing sports: A radiologic survey of the hips and knees in female ex‐athletes and population controls

Abstract: Objective. To estimate the risk of osteoarthritis (OA) of the hip and knee due to long-term weightbearing sports activity in ex-elite athletes and the general population.Methods. A retrospective cohort study was conducted of 81 female ex-elite athletes (67 middle-and long-distance runners, and 14 tennis players), currently ages 40-65, recruited from original playing records, and 977 age-matched female controls, taken from the age-sex register of the offices of a group general practice in Chingford, Northeast L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
248
9
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(265 citation statements)
references
References 18 publications
4
248
9
4
Order By: Relevance
“…Recent studies of runners (25)(26)(27)(28) reported that those who were highly physically active may face an increased risk of radiographic OA. Several small longitudinal studies (29,30) have shown no increased OA risk in runners.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of runners (25)(26)(27)(28) reported that those who were highly physically active may face an increased risk of radiographic OA. Several small longitudinal studies (29,30) have shown no increased OA risk in runners.…”
Section: Discussionmentioning
confidence: 99%
“…The precise etiology of osteoarthritis (OA) is unknown; however, several risk factors have been identified, including age (1,2), female sex (3), and both occupational (4,5) and sports-related joint stress (6)(7)(8)(9). The most important modifiable risk factor for the development and progression of OA is obesity (1,(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…This may be attributable to the cumulative physical activity that they encounter during the years of service required to reach their current rank level. Several studies that have examined former recreational and professional athletes have shown a positive correlation between various sports participation and an increased prevalence of hip OA (33)(34)(35)(36)(37)(38)(39)(40)(41). A retrospective case-control study of regular high-mileage, long-distance male runners who were longitudinally followed for 15 years found radiologic evidence of OA consisting of subchondral sclerosis (59%) and osteophyte formation (29%) in their cohort (39).…”
mentioning
confidence: 99%
“…Additionally, 30% of these runners at age 42 years had symptomatic hip pain, and their long-term, high-intensity, high-mileage running was found to be statistically equivalent to age as a risk factor for the development of radiographic hip OA and symptomatic hip pain. Prolonged exposure to higher levels of recreational physical activity has been reported to have a statistically significant increase in the risk of developing radiographic symptomatic hip OA in women and men ranging from a factor of 2 to 4.5, respectively (37,40,41). In contrast, several surveys have found no increased risk for the development of hip OA secondary to running or increased physical activity levels (42)(43)(44)(45).…”
mentioning
confidence: 99%